1997
DOI: 10.1164/ajrccm.156.5.9701098
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variability of Lung Inflammation in Cystic Fibrosis

Abstract: Chest radiography in patients with cystic fibrosis (CF) frequently shows more severe changes in the upper lobes. We performed bronchoalveolar lavage (BAL) on 12 clinically stable, young adult patients with CF to determine whether inflammation varies significantly among geographically distinct areas of the lung. We found that absolute numbers of neutrophils were generally greater in BAL fluid from the upper lobe (25.7 +/- 7.9 x 10(5) neutrophils/ml [mean +/- SEM]) of the right lung than that obtained from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 27 publications
6
69
0
Order By: Relevance
“…1). Early lung disease in cystic fibrosis involves upper lobes predominantly (30,31). Thus, it is not surprising that in this patient, whose baseline disease was moderate, but who presented after a period of poor adherence to home medications, these lobes showed the most dramatic effect of therapy in HP 3 He MR imaging.…”
Section: Discussionmentioning
confidence: 71%
“…1). Early lung disease in cystic fibrosis involves upper lobes predominantly (30,31). Thus, it is not surprising that in this patient, whose baseline disease was moderate, but who presented after a period of poor adherence to home medications, these lobes showed the most dramatic effect of therapy in HP 3 He MR imaging.…”
Section: Discussionmentioning
confidence: 71%
“…The neutrophil numbers in BALF of patients with CF is estimated at least two orders of magnitude higher than patients with chronic bronchitis during a period of exacerbation (44). This neutrophilic inflammation is partially explained by the stability of IL-8 within the CF lung.…”
Section: Discussionmentioning
confidence: 94%
“…In such a model of pathogenesis, we would expect the establishment of spatial heterogeneity within the lung, with regards to both inflammation and the distribution of T3SS-OFF versus T3SS-ON bacteria. Interestingly, nonhomogeneity of inflammation has long been observed in the setting of CF, as assessed both by radiologic imaging and by regional BAL of chronically infected patients (32,33). Recent studies examining explanted lungs of CF patients undergoing lung transplantation have shown that bacterial distribution within the lungs also is spatially heterogeneous (34), a pattern likewise seen for viral DNA (35).…”
Section: Discussionmentioning
confidence: 99%